The Influence of Leverage, Profitability and Company Size Towards Corporate Social Responsibility Cost of Companies Listed on Indonesia Stock Exchange (IDX) - Budidarma, I Gusti Agung Musa (JBE (Journal of Business and Economics); Volume 10 No.2, 2011 JBE UNKLAB, 2011)
This study presents the analysis of leverage, profitability and company size influences towards corporate social responsibility cost of companies listed on Indonesia Stock Exchange (IDX) period 2008-2010. The samples used were secondary data from IDX website. Samples were taken using the method of purposive sampling with a total of 172 samples of companies consists of 37 finance companies, 18 property & furniture companies, 15 mining companies, 29 trade companies, 20 services companies and 53 companies from other varieties of industries. The statistic method used are simple and multiple linear regression. The result of analysis had no significant influence of leverage, profitability and company size partially and simultaneously on corporate social responsibility for overall companies and by industries of finance, property and real estate, mining, trade and services, with an exception of significant influence of company size on corporate social responsibility for service industry.